2017
DOI: 10.1515/rehab-2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

Functional Thoracic Outlet Syndrome

Abstract: A -opracowanie koncepcji i założeń (preparing concepts) B -opracowanie metod (formulating methods) C -przeprowadzenie badań (conducting research) D -opracowanie wyników (processing results) E -interpretacja i wnioski (interpretation and conclusions) F -redakcja ostatecznej wersji (editing the final version) StreszczenieZespół Górnego Otworu Klatki Piersiowej (Thoracic Outlet Syndrom, TOS) jest jednym z najbardziej kontrowersyjnych mieszanych zespołów uciskowych (naczyniowo--nerwowych) zarówno ze względu na tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Studies have reported that some people have other conditions that give similar symptoms to CTS, such as cervical reticulopathy, thoracic outlet syndrome (TOS) or proximal median nerve incarceration. [11,12,15,17]. It follows that reliable and unambiguous diagnosis of CTS minimizes the risk of unnecessary physiotherapeutic and surgical interventions [24,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that some people have other conditions that give similar symptoms to CTS, such as cervical reticulopathy, thoracic outlet syndrome (TOS) or proximal median nerve incarceration. [11,12,15,17]. It follows that reliable and unambiguous diagnosis of CTS minimizes the risk of unnecessary physiotherapeutic and surgical interventions [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…The final CTS verification is possible thanks to electrodiagnostic and imaging methods [1,11,12]. In differential diagnosis of CTS, should be excluded: damage to the spinal cord or brachial plexus, thoracic outlet syndrome(TOS), median nerve compression in the proximal part of the upper limb or in the reentrant muscle, degenerative changes [17,18,19]. For CTS diagnostics, the Boston Questionnaire (BCTQ -Boston Carpal Tunnel Questionarie) is also used.…”
Section: Introductionmentioning
confidence: 99%